(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1990)
Detailed investigation of Lower Cretaceous of the Banish area, Southwest Iran, has been made possible by excellent exposure. One hundred and fifty samples from the Gadvan Formation were analysed, fifty of which in thin sections and the remainder as washed residues. Foraminiferal assemblages were picked and counted. Thin sections were of any use for quantitative analyses, however, they were important for defining the stratigraphic distribution of the single taxa and for correlation between facies and faunal distribution. A total of 40 species and subspecies of foraminifera were recognized, one of which, Gaudryina barnardi, is considered to be a new species. Two assemblage zones, the Choffatella decipiens and the younger Leupoldina cabri zones, are proposed. These zones, subdivided into four subzones, can be identified across most of southwestern Iran.